Interregional Competitiveness to Increase Economic Development of the Islands of North Maluku Province - Fajri Hatim; Musdar Muhammad; Muhammad Kamal; Suratno Amiro (Universitas Kristen Indonesia Toraja, 2022)
This study aims to analyze what economic sectors are the base sectors and contributions of the regency/city economic sector and classify competitiveness between regions of North Maluku province. Descriptive Methods Research. The object of research for regencies/cities in North Maluku. The data used are secondary and primary, Pdrb constant prices of regencies/cities, and North Maluku including in 2015-2019 constant prices. Techniques used Location Quotient, Shift Share Analysis, and Cluster Analysis. Research results. the district/city base sector has a competitive economic structure in North Maluku, there are Ternate cities, and there are 11 economic sectors that are based, while the Shift Share results have regional competitiveness; alternate the number of regional competitiveness in the sector as many as 12 sectors, East Halmahera the number of regional competitiveness in the sector as many as 10 sectors, Morotai Island the number of regional competitiveness in the sector as many as 7 sectors and. West Halmahera Regency Cluster Grouping Has the most cluster proximity to the region in North Maluku province. West Halmahera regency has a relationship with the regency/city of competitiveness development for the West Halmahera area Keywords:,, ,